Biosecurity awareness and education in Southeast Asia - Trajano, Julius Cesar Imperial (2025)
ASEAN leaders recognise the critical importance of biosecurity. But there is a need to enhance the security culture and biosecurity awareness among life science, medical, and biotechnology professionals to mitigate the misuse of biological materials.